Application of the Model-Eliciting Activities (MEAs) Learning Model on Mathematics Learning Based on higher-order thinking Skills (HOTS) - Al Ayyubi, Ibnu Imam; Widiani, Erina; Suryana, Irfan; Andriani, Anita; Sari, Desi Wulan (Noumerico: Journal of Technology in Mathematics Education, 2024)
The MEAs learning model is interactive, utilising technology, simulations, and creative methods to stimulate curiosity in students. This study aims to know whether or not significant differences occur in Mathematics learning by applying the Model-Eliciting Activities (MEAs) learning model based on higher-order thinking Skills (HOTS). Besides that, it is expected to provide a perspective on the effectiveness of the learning model in improving the quality of mathematics learning based on HOTS. This study was conducted at SMPN 1 Wanayasa with a quantitative research approach. The research method was a survey method and one-way ANOVA test analysis to see the relationship between students’ learning outcomes of class VIII A, B, C, D, E, and F. The population of this study was students at SMPN 1 Wanayasa with a sample of 191 students of class VIII consisting of 31 students in class VIII A and 32 students in classes B, C, D, E, and F. The results show that students’ learning outcomes differ only between classes VIII A and VIII D and between classes VIII C and VIII D